Unity in Diversity: Examining Religious Moderation across Religions in Indonesia - Maulana, Muhamad; Alifia Putri, Nabila Nindya; Fahira, Zihan (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2024)
Indonesia's rich religious diversity, epitomized by the concept of